Simplify by using the Distributive Property:
7a + 2( b - 4)

7a + 2( b - 4)
= 7a + 2b - 8

s

Expert answered|debnjerry|Points 37035|

Question

Asked 9/15/2012 12:52:12 PM

Updated 6/2/2014 11:38:14 AM

0 Answers/Comments

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [6/2/2014 11:38:14 AM]

Rating

There are no new answers.

Simplify by using the Distributive Property:
7( x + 8 ) + 9( x + 1)

Question

Updated 7/31/2014 12:32:52 PM

1 Answer/Comment

7( x + 8 ) + 9( x + 1)

= 7x + 56 + 9x + 9

= 16x + 65

= 7x + 56 + 9x + 9

= 16x + 65

Added 7/31/2014 12:32:52 PM

This answer has been confirmed as correct and helpful.

14 – 10 ÷ 2 x 6 + 6 : simplify by using PEMDAS **Weegy:** 6 x 3 + 10 ? 2 = 18+5 = 23 (More)

Question

Not Answered

Updated 6/2/2014 11:35:57 AM

1 Answer/Comment

14 – 10 ÷ 2 x 6 + 6;

14 - 5 x 6 + 6;

14 - 30 + 6;

14 - 24 = -10

14 - 5 x 6 + 6;

14 - 30 + 6;

14 - 24 = -10

Added 6/2/2014 11:35:56 AM

This answer has been confirmed as correct and helpful.

Simplify by using the Distributive Property:
7( x + 8 ) + 9( x + 1) **Weegy:** (7x + 56) + (9x + 9) (More)

Question

Expert Answered

Updated 6/2/2014 11:40:44 AM

1 Answer/Comment

7( x + 8 ) + 9( x + 1);

7x + 56 + 9x + 9 = 16x + 65

7x + 56 + 9x + 9 = 16x + 65

Added 6/2/2014 11:40:44 AM

This answer has been confirmed as correct and helpful.

Simplify by using the Distributive Property:
3( 2a - 5b + 6) **Weegy:** 3( 2a - 5b + 6) =3(2a)-3(5b)+3(6)=6a-15b+18 (More)

Question

Expert Answered

Updated 6/2/2014 11:37:59 AM

0 Answers/Comments

Simplify by using the Distributive Property:
3( 2a - 5b + 6)

Question

Updated 6/21/2014 12:08:25 PM

1 Answer/Comment

3( 2a - 5b + 6) = 6a - 15b + 18

3 * 2a = 6a;

3 * (-5b) = -15b;

3 * 6 = 18

3 * 2a = 6a;

3 * (-5b) = -15b;

3 * 6 = 18

Added 6/21/2014 12:08:25 PM

This answer has been confirmed as correct and helpful.

31,997,701

questions answered

There are no comments.